DEVELOPMENT OF E-LEARNING USING MOODLE APPLICATION ON MODEL PEMBELAJARAN SUBJECT IN EDUCATION TECHNOLOGY MASTER DEGREE UNIVERSITY OF MULAWARMAN - Zaenab Hanim; Karina Octavira; Rahmat Soe’oed (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This research was conducted to develop E-Learning Instructional Media using Moodle on Model Pembelajaran subject for Education Technology students of Master’s Degree in Mulawarman University. The purpose of this research are to develop the E-learning procedure development using Moodle on Model Pembelajaran subject for Education Technology students of Master’s Degree in Mulawarman University. This type of research is the Research and Development using ADDIE development model. This research is experimented tothe 2017 generation Education Technology Master’s Studentin University of Mulawarman. The data are validated by media experts, content experts, individual testing, small group testing and field tests using a questionnaire,thenthe data were analyzed with qualitative, quantitative and another statistical analysis methods. The research finding shown an instructional product using E-learning.